Analisis Miskonsepsi Matematis Kelas IX SMPN 2 Teluk Jambe Barat Materi Kubus dan Balok - Khairiah Rahmiati; Lessa Roesdiana (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
The research aims to describe students' mathematical misconceptions on cube and block based on the misconception indicators according to Sriati (in Ramadhan, 2017). This research uses qualitative research methods with descriptive research. The research subjects were 35 students of ninth grade at SMPN 2 Teluk Jambe Barat with data collection techniques is observations and tests. The results of the study, it was found that there were still many students with mathematical misconceptions on cube and block, both translation misconceptions, concept misconceptions, strategy misconceptions, systematic misconceptions, sign misconceptions. Based on the categorization formulated by Arikunto (2009), there were 29 students in medium category and 6 students in low category and no students in high category. The result of percentag subject.s mathematical misconceptions is 52.38% for translation misconceptions, 86.75% for concept misconceptions, 91.06% for strategy misconceptions, 68.92% for systematic misconceptions, and 88.90% for sign misconceptions.